Synthesis of 2,3-Dihydrosiloles via Palladium-Catalyzed Heck-type Arylation of Silacyclopentenes with Aryl Iodides - Huang, Wei-Sheng; Ling, Fang-Ying; Fang, Xiao-Jun; Cui, Yu-Ming; Ye, Fei; Xu, Zheng; Cao, Jian; Yang, Hua; Xu, Li-Wen (Synthesis, 2023)
The transition-metal-catalyzed synthesis of chiral silacycles is a challenging processes in organosilicon chemistry. Herein, we report a facile and regioselective synthesis of a novel class of 2,3-dihydrosilole derivatives with good yields via the palladium-catalyzed Heck-type reaction of silacyclopentenes (SCPs) with aryl iodides. Preliminary investigations on the enantioselective version of this palladium-catalyzed Heck-type process reveal that the presence of N-Boc-l-proline allows the diastereo- and enantioselective formation of chiral 2,3-dihydrosilole derivatives bearing both carbon and silicon-stereogenic centers.
Keywords: silacycles; palladium catalysis; Heck arylation; silicon-stereogenic; organosilicon